Effect of soaking time on the machinical properties of anealed cold-drawn low carbon steel (2012)
The paper presents the results of investigation on the effect of soaking time on the yield strength, ductility and hardness properties of annealed cold-drawn low carbon steel. The low carbon steel cold-drawn at 40% deformation was annealed at 900 deg Celsius for soaking times of 10, 20, 30, 40, 50 and 60 minutes. Tensile, charpy and Brinnel hardness tests were conducted to determine the yield strengths, tensile strengths, impact strengths, ductility and hardness of the an- nealed steel with increasing soaking time. The yield strength, tensile strength, hardness and impact strength of the steel showed a continuous drop in value with increasing soaking time up to 60 minutes with a steep drop between 30 and 40 minutes. Ductility values followed the same decreasing trend up to 40 minutes soaking time after which the values started increasing again till 60 minutes soaking time. There was a linear relationship between the tensile strength and hardness of the material for different soaking times. This linear relationship was also observed for yield strength and hardness of the material.